The biosensing performance and electrochemical properties of carbonised electrospun nanofiber: article - Shafiei, Ahmad Deedat; Tan, Huey Ling (2019)
Biosensor is one of the most important analytical devices to be used in analysing analyte where the analyte is referring to any substance whose chemical constituents are being identified and measured. There are several compulsory components to make up a fully functional biosensor. By principle, a biosensor must consist of sample, analyte, bioreceptor and transducer. Transducer plays an important role in biosensing as it converts physical quantitative and qualitative measurement and convert those values into electrical signal. Transducer is also known as sensing platform. In order transducer to become biologically capable in detecting the presence of analyte, bioreceptors or biosensing elements are required to be integrated with the support of transducer. In this research, our main concern is to find the best type of electrospun nanofiber that is used as the support for the transducer of the glucose monitoring biosensor. Thus, there were several PAA/PAN-based electrospun nanofibers used and each of the nanofibers has different associated nanoparticle fabricated together with the PAA/PAN polymer. The nanofibers were used to be immobilised with (GOx) enzyme. The biosensing performance were analysed by using several analyses mainly electro impedence spectroscopy (EIS), capacitance-voltage profiling (CV-plot), scan rate dependent study and chemical concentration dependent study. From this research, we have summarized that the presence of reduce Graphene oxide nanoparticles (rGO NPs) in Sample 2 improved conductivity of the electrospun nanofiber.